Understanding the deterrent impact formal and informal sanctions have on illegal smartphone use while driving. (September 2020) - Kaviani, F.; Young, K.L.; Robards, B.; Koppel, S.
Highlights: Survey of 2774 Victorian drivers reveals 37.1 % use smartphone illegally. Age, gender, and informal deterrent mechanisms predictors of illegal smartphone use. No formal deterrent mechanisms are significant predictors of illegal use. Countermeasures should focus on leveraging informal sanctions to reduce illegal use. Abstract: The illegal use of a smartphone while driving increases the risk of crashes. As such, road authorities rely on countermeasures to reduce illegal smartphone use. Deterrence-based methods dominate road safety, however, perceptions and impact of formal (legal) and informal (non-legal) methods to deter illegal smartphone use in Australia have not yet been explored. The current study reports on a survey of 2774 drivers (47.0 % males) that own and regularly use a smartphone. The survey analysed the self-reported frequency of illegal smartphone use while driving, perceptions of formal and informal deterrence mechanisms, differences between perceived and informed deterrence, and deterrent predictors of illegal use. The findings revealed that illegal smartphone use is increasing in Victoria, Australia. Drivers that break the law perceive deterrent mechanisms significantly different from drivers that abide by the law, however, both groups view the prospect of hurting oneself as most impactful. Additionally, drivers tend to underestimate the consequences of illegal use, yet overestimate the certainty of apprehension. A binary logistic regression analysis revealed that only age, gender and informal sanctions such as social loss (stigma/peer disapproval), internal loss (shame/guilt/embarrassment), and physical loss (injury/property damage) were significant predictors of illegal use. None of the formal mechanisms were significant. Based on these findings, road safety interventions and future research should consider exploring the psychological characteristics of young people's perceptions of informal sanctions such as social loss (shame/embarrassment) and internal loss (guilt).